"I just can't go back": Challenging Places for Older Americans since the COVID-19 Pandemic Onset - Jessica Finlay; Viveka Guzman; Gabriella Meltzer; Brendan O'Shea; Jarmin Yeh (Elsevier, 2024)
During the pandemic, many older adults felt 'out of place' in their home, work, and community spaces with potentially long-term consequences for health and wellbeing. Using national data from the COVID-19 Coping Study, thematic analysis of online long-answer responses (n = 1171; mean age 68 years; 71% female; 93% non-Hispanic White; 86% with at least a 4-year college degree; data collected April-June 2022) identified four themes regarding why particular places are challenging since the pandemic onset: (1) viral exposure fears, (2) frustrating regulations, (3) uncomfortable and hostile social dynamics, and (4) 'out of place' negative emotions. Participants also shared how they continuously address or adapt to place-based challenges through lifestyle adjustments and coping strategies. Novel findings may inform multi-scalar policymaking and interventions to support wellbeing in later life in times of stress and instability.